2020
DOI: 10.1093/ibd/izaa078
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Practice of Adalimumab and Infliximab Biosimilar Treatment in Adult Patients With Crohn’s Disease

Abstract: Abstract The introduction of tumor necrosis factor (TNF) inhibitors has significantly changed the treatment landscape in Crohn’s disease (CD). The overall therapeutic achievements with TNF inhibitors such as infliximab, adalimumab, and certolizumab pegol paved the way to push the boundaries of treatment goals beyond symptomatic relief and toward cessation of objective signs of inflammation, including endoscopic remission. Even though these agents are widely used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 108 publications
0
10
0
1
Order By: Relevance
“…5 The introduction of biosimilars in clinical practice has raised a number of concerns, namely the extrapolation from other indications to IBD and the potential for subtle differences in attributes and tertiary and quaternary structure to result in increased immunogenicity. 6 Randomized trials 7,8 and prospective cohort studies [9][10][11] have not found convincing evidence for any of these reservations with single switches This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial License (http://creativecommons.org/ licenses/by-nc/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited. For commercial re-use, please contact journals.permissions@oup.com from originator to biosimilar.…”
Section: Introductionmentioning
confidence: 99%
“…5 The introduction of biosimilars in clinical practice has raised a number of concerns, namely the extrapolation from other indications to IBD and the potential for subtle differences in attributes and tertiary and quaternary structure to result in increased immunogenicity. 6 Randomized trials 7,8 and prospective cohort studies [9][10][11] have not found convincing evidence for any of these reservations with single switches This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial License (http://creativecommons.org/ licenses/by-nc/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited. For commercial re-use, please contact journals.permissions@oup.com from originator to biosimilar.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of SC infliximab has shifted the landscape for anti-TNF therapy, among further advantages (Table 1 ). In the past, physicians could use infliximab for continuous IV therapy and adalimumab for continuous SC therapy in IBD [ 51 ], with additional SC anti-TNF options (including etanercept and golimumab) available for rheumatic diseases [ 42 ]. With only a few anti-TNF biologics available with dual formulations, a combination of IV loading and SC maintenance dosing was not a readily available option, although it may carry significant advantages for patients (including high peak serum drug levels with IV induction and constant serum drug levels with SC maintenance) [ 35 , 52 ].…”
Section: Clinical Evidence and Implications Of Sc Infliximab Prior To The Covid-19 Pandemicmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, SC anti-TNF agents were employed depending on patient preferences and physician recommendations [ 51 ], with surveys suggesting that both patients and physicians in rheumatology and gastroenterology settings prefer SC to IV biologics [ 53 55 ]. A survey of patients and HCPs from rheumatology clinics in Denmark revealed that 71% of patients currently self-injecting their treatment at home, 77% of biologic-naïve patients, and 87% of HCPs preferred the SC route of administration [ 53 ].…”
Section: Clinical Evidence and Implications Of Sc Infliximab Prior To The Covid-19 Pandemicmentioning
confidence: 99%
“…One approach is for clinicians to develop standardized treatment guidelines for biosimilars. For a recent example of the development of treatment algorithms and decision trees for various clinical scenarios, consider the review article by Reinisch et al on the use of infliximab and adalimumab biosimilars in the treatment of moderate-to-severe Crohn’s disease [ 36 ]. Greater standardization has the benefit of reducing negative outcomes from variance introduced by treatment setting and clinician experience/expertise.…”
Section: The Path Forwardmentioning
confidence: 99%